ANALISIS FAKTOR KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS PUNDONG BANTUL YOGYAKARTA - Purwaningsih, Eni; Pamungkasih, Wahyu; Hanifatun Fajria, Siti; Supatmi; Novita Kumalasari, Dian (Jurnal Riset Daerah, 2024)
Stunting is a serious public health problem and reflects chronic malnutrition that occurs during a child's growth period. The Indonesian Nutrition Status Survey (SSGI) reported a stunting prevalence of 21.6% in 2022, a small decrease from 24.4% in 2021, but still above the 2024 target of 14%. In 2023, the prevalence will stabilize at around 21.5%. Stunting not only impacts a child's physical growth, but can also disrupt cognitive development and productivity in the future. To analyze factors in the incidence of stunting in children aged 0-5 years in the work area of ​​the Pundong Community Health Center, Bantul, Yogyakarta. Using a quantitative approach with a cross-sectional research design. The population of this study was stunted children aged 0-5 years who were registered at the Pundong Community Health Center, with samples taken by total sampling. This research involved 178 respondents, of which 78.1% experienced stunting, with 21.9% in the very short category. Most of the respondents were male (56.18%) and aged between 13-24 months (37.08%). Analysis shows that chronic energy deficiency (CED) in pregnant women is the dominant factor influencing the incidence of stunting (P < 0.05). Other influencing factors are early initiation of breastfeeding, exclusive breastfeeding, maternal education, and a history of anemia in pregnant women. Chronic Energy Deficiency in mothers during pregnancy is the dominant factor influencing the incidence of stunting in toddlers. Therefore, increasing understanding of pregnant women's nutrition is very important. Exclusive breastfeeding during the first six months of life is also crucial in preventing stunting. Integrated efforts to improve the nutritional status of pregnant women and education about nutrition during pregnancy and breastfeeding are needed to reduce stunting rates in Indonesia.